2016
DOI: 10.1002/geot.201600013
|View full text |Cite
|
Sign up to set email alerts
|

Backfill of segmental lining – State of the art, redistribution behaviour of pea gravel, possible improvements / Tübbingbettung – Stand der Technik, Umlagerungsverhalten von Perlkies, Verbesserungspotenzial

Abstract: Backfill of segmental lining -State of the art, redistribution behaviour of pea gravel, possible improvements Tübbingbettung -Stand der Technik, Umlagerungs verhalten von Perlkies, VerbesserungspotenzialWith mechanized shield tunnelling the quality of the backfill is of significant importance for the stability of the lining. The used material affects the interaction between support and rock mass. Therefore, the choice of a proper backfilling material is of great importance for the system behaviour. Scaled mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…without active face support), the following basic considerations and experience should be considered: -The unsupported length is at least the shield length and despite the gentle excavation process, it has to be assumed that each potentially unstable block will actually fail in the shield area. -The pea gravel filling of the annular gap normally leads to a slope in the annular gap as a result of the internal angle of friction and the shear forces between pea gravel, rock mass and precast concrete segments [7]. Above all in the case of the frequently expected discontinuity controlled block failure these construction states either have to be appropriately considered in the design of the segments or in the backfilling concept.…”
Section: Applied Methodsmentioning
confidence: 99%
“…without active face support), the following basic considerations and experience should be considered: -The unsupported length is at least the shield length and despite the gentle excavation process, it has to be assumed that each potentially unstable block will actually fail in the shield area. -The pea gravel filling of the annular gap normally leads to a slope in the annular gap as a result of the internal angle of friction and the shear forces between pea gravel, rock mass and precast concrete segments [7]. Above all in the case of the frequently expected discontinuity controlled block failure these construction states either have to be appropriately considered in the design of the segments or in the backfilling concept.…”
Section: Applied Methodsmentioning
confidence: 99%
“…Model tests [3] on the relocation behaviour of pea gravel have shown that during the re-gripping process of the shield tail a distinct failure development takes place within the annular gap. Hence, the first ring behind the shield tail experiences an unfavourable bedding situation.…”
Section: State Of the Artmentioning
confidence: 99%
“…Since neither a single test procedure nor uniform test specimen dimensions are defined, the results of the differ- [3] ent tests are difficult to compare. Therefore, the use of certain parameters in the design phase in this way must be reviewed critically.…”
Section: Deformation Measurements Of Pea Gravelmentioning
confidence: 99%
“…In order to create an immediate contact between the segmental lining and the rock mass, a concept has been developed that can guarantee an immediate bedding behind the shield tail [4]. In this case, folded geotextile tubes (Bullflex) are attached to the exterior surface of the segments in a slot, in order to allow a damage free passage at the shield tail seal.…”
Section: Improvement Of the Bedding Behind The Shield Tailmentioning
confidence: 99%
“…A disadvantage of backfilling with pea gravel is the uneven distribution immediately behind the shield tail. Model tests have shown that a cone forms slightly below the shield tail to the crown ( Figure 1) [4]. This effect is further triggered at double shield TBMs due to the rapid movement of the gripper shield.…”
Section: Introductionmentioning
confidence: 98%